Advancing integrated water storage to support the water–energy– food–ecosystems nexus in the Blue Nile Basin, Ethiopia - Taye, Meron Teferi; Ebrahim, Girma Yimer; Lautze, Jonathan F.; Seid, Abdulkarim; Tafesse, Yonas (International Water Management Institute, 2024)
A workshop for the Tana-Beles Sub-basin (upper Blue Nile Basin), organized by IWMI, presented NEXUS Gains research results for enhancing the resilience of water–energy–food–ecosystems (WEFE) sectors through implementing integrated water storage.